EFEKTIVITAS SISTEM PENGOLAHAN LIMBAH TERHADAP KUALITAS LIMBAH CAIR PUSKESMAS KOTA PEKANBARU - Khamidah Khamidah; Zulfan Saam; Sofia Anita (Jurnal Ilmu Lingkungan, 2018)
In response to the increasing level of environmental pollution, the waste management of the health center is carried out. This study aims to determine the components in the treatment of liquid waste, the effectiveness of the quality of liquid waste and the impact of wastewater from the health center. The study population was all health centers in the city of Pekanbaru which amounted to 21. The number of samples was 8 health centers which were selected using purposive sampling technique. Research respondents consisted of the head of the health center, sanitarian staff, third parties from the health service and the community living around the health center. Analysis of the data used is descriptive analysis with comparative methods that is comparing the results of the analysis of the quality of wastewater with the quality standards of waste according to Minister of Environment Regulation numbers. 5 of 2014.The results of the study showed that the human resources of health center in the city of Pekanbaru were adequate, namely bachelor of environmental health. Fund allocation of 7 health centers is from the Pekanbaru City Health Office. The facilities and infrastructure of the WWTP (Water Waste Treatment Plan) health center have suffered a lot of damage such as sewerage, control tubs and WWTP machine cables. The wastewater treatment method used is biologically (bacteriology) mixed with chlorine and oxidation reduction. The liquid waste treatment of health centers in the city of Pekanbaru has not been effective. Only 1 health center that can be analyzed is the quality of WWTP with BOD results of 2.35 mg / L COD 100 mg / L, TSS 8 mg / L, temperature 31oC and pH 7.51. These results indicate that the COD parameter exceeds the specified quality standard of 80 mg / L. The results of interviews with the community around the health center indicate aspects of the community around the health center in the city of Pekanbaru. This is because soil and water pollution due to liquid waste cannot be directly felt, but requires a relatively long time.